New Methodical Tourism Heritages Gained in Tokyo 2020 Summer Olympic Games Duiıng the Pandemic Process - Hande KÖSE; Çetin ÖZDİLEK; Halil BİŞGİN (ümit doğan üstün, 2023)
Japan intended to utilise the Tokyo 2020 games as a means to regain the confidence and rectify the damage to the tourism industry caused by the earthquake, tsunami, and Fukushima nuclear reactor incident. Nevertheless, in response to the pandemic crisis, novel strategies and initiatives were devised with the intention of organising the games with restricted participation, thereby mitigating the achievement of the intended tourism objectives. The projects utilised in the games received complete endorsement from the IOC and were included in the roster of recommendations for future game implementations. Our research in this context focuses on analysing the newly developed methodical tourism heritages for the games. We used the document analysis technique, which is a qualitative research method. Our research focused on evaluating projects related to agora houses, digitalization, artistic works, and the exhibition of national identity. It is significant as it allows for the examination of Olympic history's pioneering achievements.